2010
DOI: 10.1111/j.1439-0388.2010.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between categorical morphological traits in Nelore cattle by applying Bayesian analysis under a threshold animal model

Abstract: In this study, Bayesian analysis under a threshold animal model was used to estimate genetic correlations between morphological traits (body structure, finishing precocity and muscling) in Nelore cattle evaluated at weaning and yearling. Visual scores obtained from 7651 Nelore cattle at weaning and from 4155 animals at yearling, belonging to the Brazilian Nelore Program, were used. Genetic parameters for the morphological traits were estimated by two-trait Bayesian analysis under a threshold animal model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
8
10
0
1
Order By: Relevance
“…This implies that the positioning of the navel, prepuce, and sheath, on average, are suitable for animals at pasture (Josahkian et al 2003). E and P had mean scores of 4.19 and 3.87, respectively, in line with those described by Faria et al (2010) The initial weight on test was 232.93 kg with a mean age of 330.20 days (Table 2) and weight corrected for 365 days was 257.48 kg, higher than found by Malhado et al (2010) who obtained 229.16 kg at 365 days with Nelore animals reared at pasture in Northern Brazil and close to that seen by Yokoo et al (2010), which was adjusted for 365 days to 250.39 kg. Average final weight adjusted for 550 days was 354.71 kg, close to that described by Yokoo et al (2010) with 347.14 kg and by Koury Filho et al (2009) who reported 330.91 kg with a mean age of 523.10 days.…”
Section: Resultssupporting
confidence: 85%
“…This implies that the positioning of the navel, prepuce, and sheath, on average, are suitable for animals at pasture (Josahkian et al 2003). E and P had mean scores of 4.19 and 3.87, respectively, in line with those described by Faria et al (2010) The initial weight on test was 232.93 kg with a mean age of 330.20 days (Table 2) and weight corrected for 365 days was 257.48 kg, higher than found by Malhado et al (2010) who obtained 229.16 kg at 365 days with Nelore animals reared at pasture in Northern Brazil and close to that seen by Yokoo et al (2010), which was adjusted for 365 days to 250.39 kg. Average final weight adjusted for 550 days was 354.71 kg, close to that described by Yokoo et al (2010) with 347.14 kg and by Koury Filho et al (2009) who reported 330.91 kg with a mean age of 523.10 days.…”
Section: Resultssupporting
confidence: 85%
“…In Ireland,McHugh et al (2012) estimated that heritability of the muscularity traits varied from 0.27 for loin development and thigh width to 0.32 for hind quarter development, width at withers and development of inner thigh. The heritabilities estimated in the present study are similar to those reported in the literature for animals of the Nellore breed(Yokoo et al 2009;Faria et al 2010). Using a sample from the same data set, Boligon et al(2011) estimated heritabilities of 0.24 AE 0.02, 0.31 AE 0.02 and 0.32 AE 0.02 for conformation, finishing and muscling scores obtained at yearling, respectively.…”
supporting
confidence: 87%
“…Higher heritability estimates were reported by Barichello et al (2010) in Canchim cattle for the same trait, which was assessed at weaning, and varied from 0.17 to 0.27. Heritability estimates for other visual score assessments in Nellore and Angus herds obtained at the weaning and yearling stages have ranged from 0.19 to 0.38 (Cardoso et al, 2004;Boligon and Albuquerque, 2010;Faria et al, 2009Faria et al, , 2010Koury Filho et al, 2010;Boligon et al, 2012;Wenceslau et al, 2012). These differences in heritability estimates could be caused by differences in the definition of visual assessment scores, the model applied to estimate the (co)variance components, as well as to differences in genetic and environmental variability between the populations or herds studied.…”
Section: Resultsmentioning
confidence: 99%